Environmental and Social Determinants of Life Satisfaction in Tehran. A Perception Study - KAZEMI, Mohammad; SAJJADI, Jhila; KALEJI, Lotfali Kouzegar; RAZAVIAN, Mohammad Taghi (Journal of Environmental Management and Tourism; Vol 8 No 7 (2017): JEMT Volume VIII Issue 7(23) Winter 2017, 2018)
The study is focused on the topic of life satisfaction of citizens in Tehran (Iran). The objective of the current study was to identify the predictive environmental and social determinants of life satisfaction. To explain the statement of the problem and form the theoretical framework, related sociological and psychological views were used. In the introduction the concept of life satisfaction is described and measurement of life satisfaction in various studies are summarized. In the empirical part a questionnaire survey is conducted that tries to determine life satisfaction of Tehran citizens (N = 385). The statistical population in this research was all citizens over the age of eighteen years in the city of Tehran and the research was conducted in 2017. Findings indicated that comparing the mean of variables shows that personal satisfaction and health status are higher than social satisfaction and justice. It is found that there is a high correlation between sense of security and life satisfaction. However, variables of sense of security and health status account for around 34% of the variations in life satisfaction. Findings of this research have important implications for making policies to improve subjective well-being through increasing the safety level and community planning.